HASAN AL-SAQAF'S CRITICISM ON THE ASSESSMENT OF THE PROPHET'S HADITH BY NAS}IR AL-DIN AL-ALBANI IN THE BOOK OF TANAQUDAT AL-ALBANI AL-WADIHAT - Siska Sukmawati; Rizki Putriani (Al-Dhikra: Jurnal Studi Quran dan Hadis, 2024)
This study aims to analyze the assessment of the hadith of the prophet by Na>s}ir al-Di>n Al-Alba>ni> in one of the hadith books of a contemporary Jordanian scholar named Hassan bin Ali Assaqaf. This research method is library research with a qualitative method that is organized descriptively, comparatively, and analytically. The book of Tanaqudhat al-Alba>ni> al-Wadihat by Hasan bin Ali Assaqaf is a book that contains corrections to Na>s}ir al-Di>n al-Alba>ni>'s mistakes in assessing the Prophetic traditions. The inconsistencies made by al-Alba>ni> made Hasan bin Ali Assaqaf examine his works to find out more about the mistakes made by al-Alba>ni>. Shaykh al-Alba>ni> is a Muslim scholar who devotes all his abilities in researching the Prophetic traditions. However, al-Alba>ni>'s efforts were countered by Hasan b. 'Ali Assaqaf because of al-Alba>ni>'s errors and inconsistencies in assessing hadith, as well as his attitude of not following the previous scholars of hadith who prioritized faith over ijtihad.